2019
DOI: 10.1002/ajmg.c.31750
|View full text |Cite
|
Sign up to set email alerts
|

Null variants and deletions in BRWD3 cause an X‐linked syndrome of mild–moderate intellectual disability, macrocephaly, and obesity: A series of 17 patients

Abstract: BRWD3 has been described as a cause of X‐linked intellectual disability, but relatively little is known about the specific phenotype. We report the largest BRWD3 patient series to date, comprising 17 males with 12 distinct null variants and 2 partial gene deletions. All patients presented with intellectual disability, which was classified as moderate (65%) or mild (35%). Behavioral issues were present in 75% of patients, including aggressive behavior, attention deficit/hyperactivity and/or autistic spectrum di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…These include genes functioning in histone modification and chromatin re‐modeling like NSD1 , EZH2 , EED2 , DNMT3A , SETD2 , SUZ12 , CHD8 (Cyrus et al, 2019; Marzin et al, 2019; Ostrowski, Zachariou, Loveday, Beleza‐Meireles, et al, 2019; Tatton‐Brown et al, 2017). Transcription factors including nuclear factor one (NFI) DNA binding proteins like NFIA , NFIB , and NFIX (Zenker et al, 2019); BRWD3 (Ostrowski, Zachariou, Loveday, Baralle, et al, 2019) and the nucleosome remodeling and deacetylase complex genes like CHD3 , CHD4 , GATAD2B also cause neurodevelopmental disorders with overgrowth, mainly macrocephaly (Pierson et al, 2019). Another group of proteins which regulate growth is the PI3K‐AKT signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include genes functioning in histone modification and chromatin re‐modeling like NSD1 , EZH2 , EED2 , DNMT3A , SETD2 , SUZ12 , CHD8 (Cyrus et al, 2019; Marzin et al, 2019; Ostrowski, Zachariou, Loveday, Beleza‐Meireles, et al, 2019; Tatton‐Brown et al, 2017). Transcription factors including nuclear factor one (NFI) DNA binding proteins like NFIA , NFIB , and NFIX (Zenker et al, 2019); BRWD3 (Ostrowski, Zachariou, Loveday, Baralle, et al, 2019) and the nucleosome remodeling and deacetylase complex genes like CHD3 , CHD4 , GATAD2B also cause neurodevelopmental disorders with overgrowth, mainly macrocephaly (Pierson et al, 2019). Another group of proteins which regulate growth is the PI3K‐AKT signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…She had multiple facial nevi and freckles, café au lait spots, and hypopigmented patches all over the body. Marked BRWD3 (Ostrowski, Zachariou, Loveday, Baralle, et al, 2019) and the nucleosome remodeling and deacetylase complex genes like CHD3, CHD4, GATAD2B also cause neurodevelopmental disorders with overgrowth, mainly macrocephaly (Pierson et al, 2019). Another group of proteins which regulate growth is the PI3K-AKT signaling pathway.…”
Section: Tsc2 (Omim*191092)mentioning
confidence: 99%
“…Previously, 32 mutations have been reported, including 21 destructive mutations (nine nonsense mutations, six frame shift mutations, three splice site mutations, and three gross deletions), seven missense mutations, one intronic mutation, and three gross duplications. 1,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Their clinical and molecular details were listed in Appendix S1 (Table S1). Further analysis demonstrated that all individuals who carrying destructive mutations were associated with intellectual disability.…”
Section: Genotype-phenotype Correlation Of Brwd3 Variantsmentioning
confidence: 99%
“…Mutant dBRWD3 (also named as ramshackle in Drosophila) leads to dying earlier during the development [8,9] or to disrupt dendritic morphogenesis and sensory organ differentiation [10]. In human, abnormal BRWD3 expression causes intellectual disability [11][12][13][14][15][16][17][18][19], leukemia [20], breast cancer [21] and head & neck cancer [22]. The human BRWD3 containing several WD repeats and 2 bromodomain (BRD) repeats, belongs to bromodomain-contain proteins (BCPs) family [12].…”
Section: Brwd3 (Bromodomain and Wd Repeat Domain Containing 3)mentioning
confidence: 99%